Planting Materials Seed Systems of Finger Millet, Rice and Taro in Jumla, Kaski and Bara Districts of Nepal - Baniya, Bimal K; Tiwari, Radha K; Chaudhary, Pashupati; Shrestha, Surendra K; Tiwari, Pushpa R (Nepal Agriculture Research Journal, 2010)
Formal and informal seed supply systems of rice (Jumla, Bara and Kaski), finger millet and taro (Kaski) were studied in three ecosites of Nepal during 1999-2001 to understand the processes of seed flow, seed production, seed selection and storage systems. A survey was conducted at 48 to 96 households. Informal seed supply was the only system in Jumla and Kaski and formal system existed only in Bara. The main sources of seed were farmer's own saved seed (67-91%), seed from neighbors and relatives. Exchange of germplasm was the main basis of fulfillment from other sources. All farmers obtained seed from their own village, while farmers introduced materials occasionally from outside village. Most of the farmers followed seed selection before or after crop harvest. Rice field selection and plant selection based on a fixed set of criteria was the common practice. Non lodged plants with more grain per panicle, bold grains, well-matured and uniform plants, long panicle, true to type, good looking grains, free from diseases and insects were the main rice seed selection criteria. All farmers from both sites stored rice seeds by local methods in the locally available containers. Mor and Mudkothi are the special straw containers to store rice seed in Bara. Dhara is a special mud structure used to store rice seeds in Jumla. Finger millet seed supply system was mostly similar to that of rice seed system. Ninety one percent farmers saved seed for their own use; however, many of them changed finger millet seeds lots or varieties regularly for their particular plot. Ears selection during harvest by set criteria for seed purpose was the common practice. Farmers stored finger millet seed carefully in small locally available containers and tried their best to maintain the quality of seed during different stage of seed production. Taro has diverse planting materials: cormels, corms with eyes, suckers and corm with small cormels. Taro planting materials management is totally informal and almost 89% farmers saved these materials for their use and replaced them mostly after 3 years. Farmers had fixed criteria of corms and cormels selection for planting purpose and focus and more on disease free. Storage of planting materials was locally by using local materials and methods. Understanding of seed system in various crops helps to develop conservation strategy. Key words: Seed flow; seed production; seed selection; seed storage; seed system DOI: 10.3126/narj.v6i0.3343 Nepal Agriculture Research Journal Vol.6 2005 pp.39-48